Využití solidních interkalárních alloštěpů k rekonstrukci po resekcích primárních kostních nádorů - Pazourek, L; Tomáš, T; Mahdal, M; Janíček, P; Černý, J; Ondrůšek, Š (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2018)
PURPOSE OF THE STUDY There are several treatment options for bone tumors at diaphyseal/metadiaphyseal sites of long bones (with joint preservation) including massive intercalary allografts, autografts (vascularized or non-vascularized fibular autograft, devitalised tumor bearing bone), endoprosthetic replacement (intercalary spacer), cementoplasty with ostheosynthesis and distraction osteogenesis. Reconstruction using massive intercalary bone allografts is for us the method of choice in case of curable primary bone tumors at the diaphyseal/metadiaphyseal region. The purpose of this study is to evaluate our results and complications. MATERIAL AND METHODS Our retrospective study reviewed 41 patients after intercalary allograft reconstruction following the resection of primary bone tumors in the years 2000 - 2014. The group consists of 27 men and 14 women with the mean age at the time of diagnosis 27 years and the mean follow-up (from primary surgery) was 7 years. The patients were diagnosed with the Ewing sarcoma (14), chondrosarcoma (9), osteosarcoma (8), adamantinoma (6), OFD-like adamantinoma (2) and aneurysmatic bone cyst (2). The site of tumor were tibia (18), femur (16), humerus (5), radius (1) and ulna (1). We retrospectively evaluated the results of this intercallary allograft reconstructions, the incidence of failures and complications as well as the role of risk factors. RESULTS 14 patients (34.1%) successfully healed without complications. In the same number of patients (14 patients, 34.1%) the allograft reconstruction failed. 7 of these patients underwent amputation (17.1%), 6 of whom for oncological complications (local recurrence) and only 1 for complications of the reconstruction (infection). Other 7 patients with an allograft-related failure were successfully treated with a limb salvage procedure and underwent a new reconstruction. The remaining 13 patients (31.7%) suffered from complications that did not result in a failure of the reconstruction. The major complications of the reconstruction were the non-union (53.7%), fractures and allograft resorption (14.6%) and infection (7.3%). By statistical evaluation of common risk factors a statistically significant relationship was found between uncomplicated healing and stable bridging osteosynthesis (p = 0.014), between allograft fractures/resorptions and non-bridging osteosynthesis (p = 0.018), and the lowest reoperation rate was connected with plate osteosynthesis (0.037). DISCUSSION AND CONCLUSIONS The intercalary allograft reconstruction is an important biological method in orthopaedic tumor surgery. Even though it is connected with a high rate of complications (non-union, fracture and resorption, infection), in the vast majority of cases they can be solved, while achieving limb-salvage and good function of extremity. The essential prerequisite for successful uncomplicated healing of reconstruction is the stable bridging osteosynthesis, preferably with a plate. In high risk patients with a combination of recognized important risk factors described in literature (adult patients, large resection (more than 15 cm), femoral location and aggressive oncological treatment) we nowadays try to reduce the complication rate with a primary combination of an allograft with vascularized fibular autograft. Key words:biological bone reconstruction, massive intercallary allograft, stable bridging osteosynthesis, primary bone tumors.
Keywords: transplantace kostí; Humans; nádory kostí; Risk Adjustment; Bone Neoplasms; rizikové faktory; Female; dospělí; zohlednění rizika; lidé; Plastic Surgery Procedures; Limb Salvage; Postoperative Complications; Adult; pooperační komplikace; ženské pohlaví; zákroky plastické chirurgie; Male; záchrana končetiny; mužské pohlaví; Bone Transplantation; Risk Factors